KU Band Proximity-Coupled Supply Based Microstrip Array Antenna for Microwave Imaging Applications - Fauzia Anis Sekar Ningrum; Yudha Riwanto (Jurnal Penelitian Pendidikan IPA, 2025)
This research focuses on the design and simulation of a 4x1 microstrip array antenna with a proximity-coupled supply technique for Ku frequency band applications, especially in microwave imaging. The antenna is designed to operate in the frequency range 12 - 16 GHz, with a resonance frequency of 14 GHz, using a Duroid 5880 substrate which has a thickness of 3.15 mm and a relative permittivity of 2.2. Array configuration and proximity-coupled techniques are applied to improve impedance matching as well as expand bandwidth. Evaluation through simulation includes important parameters such as return loss, gain, and radiation patterns. The simulation results show a return loss of -26.46 dB at a frequency of 14 GHz, which shows high transmission efficiency with minimal reflections. The radiation patterns in the azimuthal and elevation planes show consistent directivity, with stable gain throughout the frequency range. These results confirm that the designed microstrip array antenna is suitable for microwave imaging applications in the Ku band. The antenna design in this research produces high efficiency, directional radiation, and minimal signal loss, so it is able to support accurate and detailed imaging.